Efektifitas Komunikasi Vertikal Karyawan di Ruang SDM RSI Ibnu Sina Padang Panjang (Effectiveness of Vertical Communication Employees in HR Space RSI Ibnu Sina Padang Panjang): Komunikasi Vertikal, Efektifitas Komunikasi - Silvia Adi Putri; Hendry Wibowo (Jurnal Penelitian Multidisiplin, 2022)
The effectiveness of vertical communication is communication that is characterized by an understanding, can create pleasure, influence attitudes, improve good social relationships, and ultimately lead to an action. The purpose of this study is to determine the effectiveness of vertical communication employess in the SDM room of RSI Ibnu Sina Padang Panjang. The research uses descriptive method which is done by filling questioner as many as 6 respondents. The location of the study was conducted at RSI Ibnu Sina Padang Panjang Hospital, on July 24,2021 to July 31, 2021. Communication of hospital staff of RSI Ibnu Sina Padang Panjang based on IKI result is good value, while based on EKU result is enough. From the results of research can be concluded that the effectiveness of vertical communication employees in the space of SDM RSI Ibn Sina Padang Panjang using the assessment of the scale of assessment of the results of the effectiveness of vertical communication of employees running well because there is still from some point effectiveness vertical communications that have not been met from the results of questionnaires obtained from respondents , one of which is at the time of communicating has not been fully influenced by the feelings of self. It is expected that employees or supervisors at the time of communication are influenced by the feelings themselves.